2019
DOI: 10.1177/0825859719892084
|View full text |Cite
|
Sign up to set email alerts
|

Social and Health System Complexities Impacting on Decision-Making for Utilization of Oncology and Palliative Care in an African Context: A Qualitative Study

Abstract: Background: There is a dearth of research focusing on identifying the social complexities impacting on oncology and palliative care (PC), and no study has explored how the health-care system in Nigeria or other African contexts may be influencing utilization of these services. Aim: This study explored how social complexities and the organization of health-care influenced the decision-making process for the utilization of oncology and PC in a Nigerian hospital. Methods: This qualitative study used an interpreti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…This is because when patients are retained for care, they continue to pay for the services they are receiving. Payment for health care services is the key financial mechanism operational in the Nigerian health care system (Agom et al, 2020;Aregbeshola & Khan, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because when patients are retained for care, they continue to pay for the services they are receiving. Payment for health care services is the key financial mechanism operational in the Nigerian health care system (Agom et al, 2020;Aregbeshola & Khan, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…A hospital in south east Nigeria was purposively chosen for this study for reasons such as it rendered organized PC, which facilitated collection of useful data that revealed the complexities of culture being studied, proximity and accessibility which promoted prolonged engagement as well as immersion during field work. This government-owned hospital charges a fee for inpatient and outpatient cancer and PC services for individuals living in the south-eastern Nigeria and its surrounding states (Agom et al, 2020).…”
Section: Study Settingmentioning
confidence: 99%
“…In Nigeria, research has shown that most of the patients with cancer have no financial ability to pay for their services,[ 30 ] indicating that these patients may not access the services that could improve the quality of their life. In an effort to reduce the financial distress experienced by the patients, the palliative and oncology professionals provided them with financial assistance because there is no financial assistance scheme for this vulnerable group in Nigeria.…”
Section: Discussionmentioning
confidence: 99%
“…25 Given its potential for yielding the understanding of complex processes as they occur in their natural setting, qualitative case studies are being increasingly used in a wide range of health-related disciplines and fields, including medicine, nursing, and health management. 26–28 The case study method is characterized by the use of multiple sources of evidence (eg, fieldwork, semi-structured interviews, documents). As argued by Yin, case study research is an empirical investigation that examines a contemporary phenomenon within its real-life context.…”
Section: Methodsmentioning
confidence: 99%